(untitled) (SCIÉNDO INGENIUM, 2022)
The objective of the present investigation is to determine the removal of heavy metals from the RMoch6 point of the Moche river by means of commercial chitosan biopolymer. To carry out the investigation, the factorial experimental design was shown, having as independent variables the amount of chitosan and the contact time to compare the results of the treatments through the dependent variables such as the percentage of metal removal and the adsorption capacity. The results of the investigation indicate that the variable amount of chitosan has a significant effect on the adsorption capacity dependent variable and adjusts sin to the Freundlich isotherms also has an effect on the percentage of metal removal for aluminum, arsenic, cobalt, copper, iron, lead and zinc, however, for cadmium it does not have a significant effect. The results of the investigation confirm that the amount of commercial chitosan and optimal contact time to remove the highest percentage of lead, aluminum and cadmium is 7.83g, 7.75g and 8.83g and a time of 90 min. With these treatments in the water of the RMoch6 point, the removal of heavy metals such as aluminum, arsenic, cadmium, copper, iron, lead and zinc can meet the ECA, cat.3.